2008
DOI: 10.1080/02652030701711016
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing fungal and aflatoxin levels in Turkish hazelnuts (Corylus avellanaL.) during growth, harvest, drying and storage: A 3-year study

Abstract: The levels aflatoxins in Turkish hazelnuts have been monitored over a 3-years period (2002)(2003)(2004). Periodical sampling was made in 72 different orchards at different locations representative of the hazelnut-growing areas and post-harvest applications. Various parameters (aflatoxins, water activity, moulds) were analysed and environmental conditions (temperature and relative humidity) recorded during growing and at different stages of harvest and post-harvest processing, involving three different harvesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…In another study, however, a w was reported to increase at the end of the 24. months storage period (0.50-0.54) (Demirci Ercoskun, 2009). It has been reported that AF may develop if the a w exceeds 0.83 for two days (Ozay et al, 2008). The a w in our study has never exceeded 0.72 in any drying methods and storage time.…”
Section: Water Activity (A W )supporting
confidence: 45%
See 1 more Smart Citation
“…In another study, however, a w was reported to increase at the end of the 24. months storage period (0.50-0.54) (Demirci Ercoskun, 2009). It has been reported that AF may develop if the a w exceeds 0.83 for two days (Ozay et al, 2008). The a w in our study has never exceeded 0.72 in any drying methods and storage time.…”
Section: Water Activity (A W )supporting
confidence: 45%
“…The GG and CG which are a traditional drying methods, increases the mold growth and mycotoxin risk because they are not hygienic, the drying time changes depending on the climatic conditions and the product is rehydrated. For this reason, DM of hazelnut instead of drying in the sun is suggested as an effective method to prevent AF (Ozay et al, 2008) because, in natural drying conditions, the humidity value can rise very much. Despite the fact that in our work the specimens have been preserved under the common storage conditions which is suitable for the development of fungi, no AFB 1 and total AF have ever been detected in any drying methods and storage time.…”
Section: Aflatoxinmentioning
confidence: 99%
“…In Turkish hazelnuts, the mould count ranged between 1.8 Â 10 1 and 3.8 Â 10 6 CFU g À1 from flowering stages to harvest. A. flavus (89%) was found to be more common than A. parasiticus (11%) on hazelnuts cultivated in Turkey over a 3-years period (2002e2004) (Ozay et al, 2008). In similar, the high incidence of B-group AFs contamination rather than G-group in both walnuts and hazelnuts obtained present results might be due to both occurrence and invasion of nuts by A. flavus rather than A. parasiticus.…”
Section: Analysis Of Real Samplesmentioning
confidence: 47%
“…Groundnuts exported from Sudan to EU have previously been rejected owing to failure to meet aflatoxin standards (Hanafi, 1987). Thus, the purpose of reducing aflatoxin contamination levels in groundnuts should be to minimize food safety concerns and also for economic reasons (Ozay et al, 2008). A high proportion (80%) of raw groundnut samples from the cottage industry had aflatoxin levels below 10 µg/kg.…”
Section: Materials and Methods Study Sitesmentioning
confidence: 99%